APPLICATION AND CHARACTERIZATION OF IN SITU GEL - Kurniawansyah, Insan Sunan; Sopyan, Iyan; Wathoni, Nasrul; Fillah, Dasty Latifa; Praditya, Rahadianti Umi (International Journal of Applied Pharmaceutics, 2018)
Applications of in situ gel have been used for a variety of drug delivery routes, such as oral, ocular, rectal, vaginal and injection. Characterization of in situ gel was determined to ensure that the prepared preparation met the standard and it safe. This review describes every aspects of this novel application and characterization of in situ gel preparations, which present the readers an exhaustive detail and might contribute to research and development. In the chemical evaluation in situ gel determined the diffusion of the active substance of a compound by measuring its concentration. In physical evaluation of isotonic calculated by osmotic pressure, drug release was determined by melting point of the substance polymer, gel strength as measured by rheometer, homogenecity test determined by under the light, and stability test with environmental conditions setting. In microbiology evaluation determine if the preparations was contaminated or not, also be effective and safe. Ocular irritation studies-Draize Test us an animal mice or rabbit and determination of visual appearance, clarity, and pH is required. In situ gels offer the primary requirement of a successful controlled release product that is increasing patient compliance.